A1‐Adenosine receptor activation has biphasic roles in development of acute kidney injury at 4 and 24 h of reperfusion following ischaemia in rats. Issue 7 (12th June 2016) - Najafi, Houshang; Owji, Seyed Mohammad; Kamali‐Sarvestani, Eskandar; Moosavi, Seyed Mostafa Shid
Abstract : New Findings: What is the central question of this study? A1 ‐Adenosine receptor (A1 AR) blockade before renal ischaemia aggravated kidney injury after 24 h reperfusion in several studies, whereas we previously observed a renoprotective effect of A1 AR blockade during a 4 h reperfusion period. What are the underlying mechanisms for this biphasic effect of pretreatment with an A1 AR antagonist at 4 and 24 h reperfusion? What is main finding and its importance? A1 ‐Adenosine receptor blockade protects the kidney against ischaemia‐induced injury during the early hours of reperfusion by attenuating the reduction in renal blood flow and lowering energy expenditure, whereas its inflammatory effects gradually dominate over 24 h reperfusion to intensify kidney injury. We previously reported that selective blockade of the A1 ‐adenosine receptor (A1 AR) with an antagonist, 8‐cyclopentyl‐1, 3‐dipropylxanthine (DPCPX), had protective effects on renal ischaemia‐induced structural and functional disruption during a 4 h reperfusion period. In contrast, several studies demonstrated that endogenous and exogenous A1 AR activation before renal ischaemia had a renoprotective role 24 h after reperfusion, through mechanisms that reduced inflammation, necrosis and apoptosis. In this study, we investigated potential mechanisms underlying this biphasic action of A1 AR in renal ischaemia–reperfusion injury. Anaesthetized male Sprague–Dawley rats underwent 30 min of bilateral renal ischaemia, and biphasic effects of pretreatment with DPCPX at 4 and 24 h reperfusion were studied on the kidney injury. Pretreatment with DPCPX attenuated at 4 h but augmented at 24 h reperfusion the renal ischaemia‐induced histological damage, reductions in creatinine clearance, urea excretion and free‐water reabsorption, and increases in bicarbonate excretion and tissue malondialdehyde. The DPCPX increased tumour necrosis factor‐α expression and migration of lymphocytes in the postischaemic kidney at both time points, but with a different pattern; lymphocytes mostly aggregated in cortical periarterial spaces at 4 h reperfusion but had infiltrated into the interstitium at 24 h reperfusion. In conclusion, A1 AR activation contributes to ischaemia‐induced acute kidney injury during the early hours of reperfusion by causing a greater reduction in renal haemodynamics and by elevating tubular energy expenditure, which overcome its anti‐inflammatory effect. However, its anti‐inflammatory actions are exerted by reducing lymphocyte infiltration and cytokine production that begins to dominate from 4 to 24 h of reperfusion, which is reflected in attenuation of renal structural and functional disruption. Abstract :